Perioperative serum lactate as a predictor of post-operative length of hospital stay and in-hospital mortality in patients undergoing major emergency abdominal surgeries - Safura Riaz; Abdul Waheed Mir; Suhail Sidiq; Showkat Ahmed Gurcoo; Mohammad Akbar Shah; Falak Ara; Akif Mutahar Shah; Altaf Hussain Mir (Asian Journal of Medical Sciences, 2024)
Background: Major surgeries can develop metabolic acidosis during the perioperative period. Any clinical condition leading to decreased tissue oxygenation causes lactate levels to rise proportionally. Aims and Objectives: This study was aimed at evaluating perioperative serum lactate as a predictor of length of hospital stay and in-hospital mortality in patients undergoing emergency major abdominal surgeries. Materials and Methods: Adult patients posted for emergency abdominal surgical procedures were enrolled for 2 years. Patients were observed intraoperatively and lactate levels were measured. In post-operative period lactate levels were recorded for 24 h. Relationship of lactate with hospital length of stay and in-hospital mortality was analyzed. Results: Total of 93 patients were enrolled for 2 years. Mean age was 50.4 years. Mean baseline lactate was 2.95 mmol/L. Total in-hospital mortality was 16.1%. Thirteen patients had perioperative serum lactate level of ≤ 2 mmol/l, with a mean hospital length of stay of 8.6 days and no mortality. Fifty-one patients having perioperative serum lactate between 2 and 4 mmol/L, with a mean hospital length of stay of 11.2 days and mortality of 13.3%. Twenty-nine patients had serum lactate of >4 mmol/L, with a mean hospital length of stay of 17.3 days and mortality of 86.7%. Elevated serum lactate was associated with a longer length of hospital stay, with lactate at 12 h having the highest predictive value (area under curve 0.987). Similarly, lactate at 12 h had the highest accuracy at predicting mortality as per receiver operating characteristic (AUC 0.895). Conclusion: Serum lactate was associated with increased in-hospital mortality and longer length of hospital stay in emergency abdominal surgeries.